Analisis Tingkat Keselamatan Lalu Lintas Pada Persimpangan Jalan Raya Camplong STA. KM.90+208 – 90+311 Menggunakan Metode TCT - Yuwana, Wahyu; Zabadi, Fairus (SLUMP TeS : Jurnal Teknik Sipil, 2024)
Safety is a factor that is needed by every human being in this world, including safety in the transportation sector. One of the transportation safety issues that is currently receiving sharp attention is road traffic safety. Camplong District is a district that is currently in the development stage. Camplong Highway Intersection (KM.90+208 – 90+311) Camplong District, Sampang Regency has quite high density alternately on each lane during peak hours. Apart from that, the Camplong Highway intersection (KM.90+208 – 90+311 ) there are no traffic lights which makes the road prone to accidents. The aim of this research is to determine the level of traffic safety, to determine the types of vehicles involved in conflicts, and to determine conflicts that can cause accidents at the Camplong Highway Intersection (KM.90 +208 – 90+311). Analysis of the level of traffic safety at the Jalan Raya Camplong intersection using the Traffic Conflict Technique (TCT) method (case study STA. KM.90+208 – 90+311) shows that conflict incidents between drivers are included in serious conflicts which can result in accidents but not always accidents occur, the type of vehicle involved in the conflict is on average more motorbikes because the volume of motorcyclists' vehicles is greater than other vehicles, and the potential for accidents is the rider's negligence in turning intersections or crossing carelessly.